Evaluasi Keberhasilan Program Terapi Pencegahan Tuberkulosis di Puskesmas Wilayah Jakarta Barat Tahun 2024 - Dickson, Dickson; Suratmi, Tri; Samingan, Samingan (LPPM Universitas Respati Indonesia, 2025)
Tuberculosis (TBC) remains a global health challenge, including in Indonesia. Tuberculosis Preventive Therapy (TPT) is a key strategy to prevent Latent TB Infection (LTBI) from progressing to active TB. However, the 2024 TPT program achievement in West Jakarta was only 17% against a 68% target. This study aimed to evaluate the program's success at Public health centers (PHC) using a qualitative evaluative and phenomenological approach and the Context, Input, Process, Product (CIPP) model. Subjects included health office staff (1 person), PHC officers (16 people), and health cadres (8 people). Data were collected through in-depth interviews, document studies, observation, and Focus Group Discussions (FGD), and analyzed using content analysis with triangulation for validation. The results indicate that while the program follows Ministry of Health Regulation No. 67 of 2016, its implementation faces significant challenges. Limited availability of the 3HP drug regimen and low preference for the lengthy 6H regimen were major constraints. Healthcare workers faced high workloads, while community cadres had limited capacity for public education. Additional barriers included limited counseling time, negative public perceptions of TPT, and less effective cross-sectoral coordination. The overall achievement was only 17%, with large inter-area disparities (e.g., Palmerah at 67% vs. Grogol Petamburan at 12%). Low adherence to the 6H regimen further impacted outcomes. In conclusion, the success of the TPT program in West Jakarta is hindered by limited 3HP drug availability, low public understanding, and insufficient cross-sector coordination.